Drugs in Context Editorial: Review of 2020 and what lies ahead in therapeutic interventions - Sarah L Anderson; Matteo Bassetti; Arduino A Mangoni (BioExcel Publishing Ltd, 2021)
The year 2020 was dominated by the COVID-19 pandemic, bringing with it unprecedented advancements in the fields of healthcare and therapeutic interventions as well as in vaccine and drug development. Nevertheless, several other advancements in various fields of medicine also deserve attention. Herein, the Senior Editors of Drugs in Context provide us with their expert opinion on the events of 2020 and what lies ahead in 2021.